PENGARUH ELECTRONIC WORD OF MOUTH (EWOM) MELALUI AKUN INSTAGRAM @MARASOE.ID TERHADAP SIKAP KONSUMEN - Mita Hendriyani; Shinta Hartini Putri; Faisal Reza (LPPM UNIBI, 2021)
Electronic word of mouth (EWOM) is a negative or positive statement made by actual, potential, or previous consumers who talk about this product and information is available to people via the internet media. One company that utilizes Electronic word of mouth (EWOM) is Marasoe by utilizing Instagram social media. The purpose of this study was to determine the effect of intensity, Valence of opinion and Content via Instagram @ Marasoe.id on consumer attitudes. The theory used is Theory Of Reasoned Action. The research method used is quantitative using a verification approach. The data were analyzed using the regression method to find the effect and the F test and the T test for simultaneous and partial hypothesis testing. The sampling technique used random sampling to 163 respondents. The results of this study indicate that simultaneously Electronic word of mouth (EWOM) through the Intagram account Marasoe.id affects consumer attitudes. Partially the intensity, Valence of opinion and Content through the Intagram account Marasoe.id affect consumer attitudes. The value of R is 0.794 and the coefficient of determination (R Square) is 0.631 which shows an effect of 63.1%, while the remaining 36.9% is explained by other causes. The regression coefficient for X is 0.410, indicating that every 1% increase in Electronic word of mouth (EWOM) units will increase consumer attitudes by 0.410.